2019
DOI: 10.12691/education-7-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Vocational High Schools in Machining Expertise in the Labor Market in Yogyakarta, Indonesia

Abstract: The objectives of this study were: (1) to describe the outcome of the Vocational High Schools (VHSs) in the field of machining expertise in the labor market, and (2) the efforts of VHSs in increasing the distribution of graduates. The location of this study was in four VHSs in the field of nationally accredited machining expertise in the Yogyakarta. The technique of data collecting used interviews and documentation. The data analysis of this study used descriptive statistics. The results of this study are: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…Sekolah Menegah Kejuruan (SMK) merupakan salah satu lembaga pendidikan kejuruan di Indonesia yang bertujuan untuk meningkatkan kualitas pendidikan dan keterampilan serta keahlian SDM yang selaras dengan perkembangan teknologi dan berbagai perubahan (Bustanil S et al, 2019;Disas, 2018;Utami, 2017). Selain pihak penyelenggara pendidikan kejuruan, keberhasilan pendidikan kejuruan dalam meningkatkan kualitas SDM tidak terlepas dari peran serta masyarakat (Afandi & Sentot Wijanarka, 2019;Mulyanti et al, 2020). Ada dua hal yang menjadi kelebihan SMK, pertama lulusan dari institusi ini dapat mengisi peluang kerja pada dunia usaha/dunia industri karena terkait dengan dunia salah satu sertifikasi yang dimiliki oleh lulusan melalui uji kemampuan kompetensi (Nurlaela et al, 2019;Supriyadi et al, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Sekolah Menegah Kejuruan (SMK) merupakan salah satu lembaga pendidikan kejuruan di Indonesia yang bertujuan untuk meningkatkan kualitas pendidikan dan keterampilan serta keahlian SDM yang selaras dengan perkembangan teknologi dan berbagai perubahan (Bustanil S et al, 2019;Disas, 2018;Utami, 2017). Selain pihak penyelenggara pendidikan kejuruan, keberhasilan pendidikan kejuruan dalam meningkatkan kualitas SDM tidak terlepas dari peran serta masyarakat (Afandi & Sentot Wijanarka, 2019;Mulyanti et al, 2020). Ada dua hal yang menjadi kelebihan SMK, pertama lulusan dari institusi ini dapat mengisi peluang kerja pada dunia usaha/dunia industri karena terkait dengan dunia salah satu sertifikasi yang dimiliki oleh lulusan melalui uji kemampuan kompetensi (Nurlaela et al, 2019;Supriyadi et al, 2019).…”
Section: Pendahuluanunclassified
“…Praktik kerja yang telah dilakukan dapat membekali siswa dengan keterampilan, sehingga dapat bersaing baik sebagai pekerja maupun sebagai wiraswasta (Sauli, 2021;Silaban & Rizal, 2020;Stellmacher et al, 2020). Selain pihak penyelenggara pendidikan kejuruan, keberhasilan pendidikan kejuruan dalam meningkatkan kualitas SDM tidak terlepas dari peran serta masyarakat (Afandi & Sentot Wijanarka, 2019;Mulyanti et al, 2020). Pemberian pelajaran praktik secara terus menerus dan berkesinambungan yang dimaksud supaya peserta didik mengalami pembiasaan dan memiliki kemampuan yang profesional dalam menghadapi dunia kerja setelah lulus dari sekolah (Ashari et al, 2021;Janah & Winarno, 2015;Tri Astuti et al, 2019).…”
Section: Pembahasanunclassified
“…Currently, the rapid growth of the workforce is a crucial issue that is very important to pay attention to, especially the Technical and Vocational Education and Training (TVET) organization as one of the human resource development institutions (Billett, 2006;Nurtanto et al, 2020;Pavlova, 2009;Sariwulan et al, 2020). In developing countries such as Indonesia, the fact has been revealed that the number of vocational education graduates is inversely proportional to the availability of jobs that these graduates can fill (Afandi & Sentot Wijanarka, 2019;Larosa & Munadi, 2019;Sutiman et al, 2022). Data from the Central Statistics Agency (CSA) recorded the number of unemployed graduates of vocational education at 10.38% (1,876,661 people) in February 2022 (Badan Pusat Statistik, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the collaboration between the two expertise programs and the automotive industry must also be more intensive (Handayani et al, 2019). The implementation of industry-based learning and the provision of tools that exist in the industry are very important, so that the competence of graduates can meet the relevant industry qualifications to be entered (Afandi & Sentot Wijanarka, 2019).…”
Section: Introductionmentioning
confidence: 99%